Funkcje ustawowej defi nicji przygotowania do przestępstwa. Zarys problematyki - Małecki, Mikołaj (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
Article 16 § 1 of the Penal Code contains a legal definition of the preparation of the crime. According to the specifics of this regulation, we may distinguish three functions of the present regulation: 1 a pattern model of the preparatory actions; 2 the type of the offense, 3 a legal criterion, which is used to separate the preparation of a crime and the attempt to commit a crime.
Keywords: przygotowanie przestępstwa; usiłowanie; zasady wykładni prawniczej